Psychometric properties of Brief Coping Orientation to Problems Experienced in patients with multiple chronic conditions: A preliminary study. Issue 3 (1st June 2021) - Cheng, Cheng; Yang, Cong‐Yan; Inder, Kerry; Chan, Sally Wai‐Chi
Abstract: Background: Multiple chronic conditions (MCCs) are highly prevalent in primary care. Coping is an important psychological factor that influences patients' ability to adapt physically and mentally to MCCs. Testing a reliable and valid psychometric inventory is necessary to identify coping strategies before developing coping‐oriented interventions. Purpose: The purpose of this study is to examine the psychometric properties of the Chinese version of the Brief Coping Orientation to Problems Experienced (Brief COPE‐CN) inventory in patients with MCCs. Method: This study adopted a cross‐sectional design. A convenience sample of 290 Chinese patients with MCCs was recruited from a tertiary hospital in East China. The Brief COPE‐CN, sociodemographic characteristics and clinical data were collected using a self‐reported questionnaire from November 2017 to May 2018. Factor analysis and reliability analysis were performed. Results: The mean age of the participants was 58.5 years (range from 23 to 95 years), and approximately half of the participants were female (49.3%). Most participants had two chronic conditions (82.1%) and reported having had MCCs for more than 2 years. The explanatory factor analysis (EFA) identified five factors in the Brief COPE‐CN that explained 58.4% of the total variance. The Cronbach's α coefficients ranged from .65 to .85 for the five subscales. Conclusions: The psychometric properties of the Brief COPE‐CN were acceptable for use with Chinese patients with MCCs. With further evaluation, this instrument may help health‐care professionals understand patients' coping and develop coping‐based interventions to promote coping in this population. Summary statement: What is already known about this topic? There is a growing predominance of chronic diseases in China, with many Chinese patients living with multiple chronic conditions (MCCs) that can adversely impact physical and psychological health. Coping‐oriented interventions that address and enhance patients' coping strategies are beneficial in terms of improving their health. There is no valid and reliable Chinese tool to measure coping strategies among patients with MCCs. What this paper adds? This study reports a five‐factor structure of the Chinese version of the Brief Coping Orientation to Problems Experienced (Brief COPE‐CN) established by explanatory factor analysis. The five‐factor structure of the Brief COPE‐CN has good internal consistency. The implications of this paper: The five‐factor Brief COPE‐CN has the potential to measure coping strategies effectively in Chinese patients with MCCs. With further evaluation, this instrument may be a useful tool for developing specific interventions to promote coping in Chinese patients with MCCs.